1978
DOI: 10.1524/zkri.1978.148.3-4.295
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the structures of GeS, GeSe, SnS and SnSe

Abstract: The orthorhombic structures (Pbnm-Di~; No. 62) of GeS, GeSe, SnS and SnSe have been refined (X-ray diffractometer data:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
156
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(192 citation statements)
references
References 10 publications
34
156
0
2
Order By: Relevance
“…3a); no other peaks are observed that correspond to other tin oxide or sulfide species. The calculated unit cell parameters of the herzenbergite SnS films (shown in Table 1) match the expected (Pbnm) space group, with lattice parameters that closely match with those reported in literature [34,35]. The films heated at 400°C have strong, well-defined diffraction peaks.…”
Section: Resultssupporting
confidence: 82%
“…3a); no other peaks are observed that correspond to other tin oxide or sulfide species. The calculated unit cell parameters of the herzenbergite SnS films (shown in Table 1) match the expected (Pbnm) space group, with lattice parameters that closely match with those reported in literature [34,35]. The films heated at 400°C have strong, well-defined diffraction peaks.…”
Section: Resultssupporting
confidence: 82%
“…Theory (DFT-LDA) [7] Experimental [6] Present Theory (DFT-LDA) [3] Theory (DFT-GGA) [3] Theory (FP-LAPW with GGA) [3] Theory (FP-LAPW with GGA) [36] Theory (FP-LAPW with GGA) [15] Experimental [37] Experimental [38] Experimental [39] The energy band structures calculated for SnS and GeS are shown in Fig. 1.…”
Section: Ges Presentmentioning
confidence: 99%
“…In the past, some detailed works [1][2][3][4][5][6][7] have been carried out on the structural and electronic properties of these compounds. Rathor et al [3] presented the bands and density of states (DOS) using the Hartree-Fock, density functional and pseudopotential schemes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Элементарная ячейка кристалла содержит два слоя, переходящих друг в друга под действием опера-ции инверсии. Согласно [3], координаты атомов внутри элементарной ячейки, выраженные в долях параметров…”
Section: Introductionunclassified